(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The study aimed to determine the relationship between management practices of nurse supervisors and patient care satisfaction. The study used a descriptive correlational through survey-questionnaire. Purposive sampling was utilized; there were 100 staff nurses and 100 patients who participated in this study. Results showed that the nurse supervisors’ management the over-all mean score is 4.02. For the over-all mean score for patient care satisfaction is 4.01. Further, Pearson-r revealed (r = 0.10, n = 200, p = 0.31) which indicated that there was no significant relationship between the two variables being tested in the study. Conclusions includes: staff nurses are generally contented with their supervisor’s management; patients are generally appeased with the nursing care they receive; management practice of nurse supervisors has no effect on patient care satisfaction.